Mental Health and Human Rights Issues in Pakistan: Possible Clinical and Policy Measures at the national level - Hussain, Sajjad; Shah , S Naqeeb Hussain; Aziz , Khadija; Shafiq, Mohammed (International Journal of Psychosocial Rehabilitation, 2020)
Thispaper aims to explore the causes of increasing mental ailments in Pakistan and the role of professional social workers in re-adjustment of psychiatric patients into the society. In addition, the study also spotlights the importance of social work in bringing mental health and human rights issues to the front in Pakistan. The study is based on the analysis of existing literature on mental health and related issues with help from relevant books, online sources, newspapers and journals. The study concludes that mental illnesses are main contributing factors in human rights abuses that occur in Pakistan. The most affected ones are women, children and youth whoneed special attention of policy makers and professional social workers. The study recommends that – in order to tackle mental illnesses and human rights issues –the medical social workers should create awareness among the general public about the causes and implications of psychiatric disorders and guide family members of such patients regarding treatment, rehabilitation and follow-up.For this aim to be achieved, the study recommendscapacity building of social workers towards effectiveness of their serviceswhile assisting the psychiatric patients.